Cross hedging with stock index futures - Zainudin, Ahmad Danial; Mohamad, Azhar (Elsevier, 2021)
This paper examines the cross hedging effectiveness between UK FTSE100 and world stock index futures from developed and emerging markets: the US, Australia, Brazil, Japan, Hong Kong, Korea and Malaysia. Our daily dataset spans from August 2002 through November 2019. We apply the OLS, VECM and Maximal Overlap Discrete Wavelet Transform (MODWT) to calculate the optimal cross hedge ratio and cross hedging effectiveness. Our empirical results show that the US E-Mini DJIA$5 futures contract is the best cross hedging instrument for the UK FTSE100, followed by the Australia S&P/ASX 200. The multiscale cross hedging effectiveness results from the MODWT estimation suggest the optimal hedging period of more than 256 days with the US E-Mini DJIA$5 and Australia S&P/ASX 200 futures.